2019
DOI: 10.1111/jcmm.14463
|View full text |Cite
|
Sign up to set email alerts
|

miR‐1, miR‐499 and miR‐208 are sensitive markers to diagnose sudden death due to early acute myocardial infarction

Abstract: MicroRNAs (miRNAs) are strongly up‐regulated under pathological stress and in a wide range of diseases. In recent years, miRNAs are under investigation for their potential use as biomarkers in cardiovascular diseases. We investigate whether specific cardio‐miRNAs are overexpressed in heart samples from subjects deceased for acute myocardial infarction (AMI) or sudden cardiac death (SCD), and whether miRNA could help differentiate between them. Forty four cases of death due to cardiovascular disease were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 70 publications
4
50
0
Order By: Relevance
“…The importance of biomarkers in forensics to differentiate between different cardiac events such as sudden cardiac death, arteriosclerosis, and MI is underlined by Pinchi et al and Dlouhá et al [ 52 , 53 ]. They stated that the pathology of MI needs to be investigated as a cause of sudden cardiovascular death and therefore tested certain microRNAs for their potential of distinguishing between sudden cardiac death and MI.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of biomarkers in forensics to differentiate between different cardiac events such as sudden cardiac death, arteriosclerosis, and MI is underlined by Pinchi et al and Dlouhá et al [ 52 , 53 ]. They stated that the pathology of MI needs to be investigated as a cause of sudden cardiovascular death and therefore tested certain microRNAs for their potential of distinguishing between sudden cardiac death and MI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the miRNAs which are affected by cardiopulmonary bypass are known to initiate cardioprotective mechanisms. Previous studies demonstrated that miR-1, miR-499 and miR-208 are associated with and contribute to the pathophysiology mechanisms of IR-injury in patients with acute myocardial infarction [16,17]. Nevertheless, there are only few studies that have investigated the changes of miRNA profiles during cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The level of miR-1 down-regulation was increased with prolonged time of MI in rats, and also with prolonged time of post-hypoxic reoxygenation in H9c2 cells [48]. MiR-1 was found to be down-regulated also in heart tissues obtained by post-mortem autopsies from infarcted human hearts [52,53]. When the infarcted hearts were divided into subgroups according to the duration of MI, tissue expression of miR-1 was down-regulated only in the subgroup with more than one day and less than seven days old MI, in which signs of total coagulation necrosis and loss of nuclei accompanied by edema and neutrophil infiltration of the interstitium was observed [52].…”
Section: Role Of Mir-1 In Cardiac I/r Injurymentioning
confidence: 99%
“…↓miR-1 in heart tissue in response to I/R in rats, mice, and infarcted human hearts [48][49][50]52,53] ↓miR-1 in H9c2 cells and neonatal cardiac myocytes in response to H/R [48,51] ↑miR-1 in remote myocardium compared to infarcted zone or healthy hearts in infarcted human hearts [54] ↑levels of circulating miR-1 after AMI in pigs and humans [58,59] miR-1 overexpression exacerbated cardiac I/R injury in transgenic mice [55] miR-1 inhibition protects against I/R (H/R) injury in rats, mice, and H9c2 cells [48,55,56] miR-21…”
Section: Type Of Cvd Mir Findings Referencementioning
confidence: 99%